An Excerpt from "S’intelligèntzia de Elias" by Giuseppe Coròngiu, Translated into Galician - Basalo Bembibre, Pedro (Madrygal. Revista de Estudios Gallegos, 2023)
Galician translation of the Preface to S’intelligèntzia de Elias by Giuseppe Coròngiu.